Report of Working Group on Shipbuilding and Shiprepair Industry For The Seventh Five Year Plan (1985-90) - Planning Commission (Planning Commission, 1984)
To review the performance of the ship building as well as ship repair industry during the Sixth Plan period along with an analysis of demand, capacity and production (estimates) in 1984-85 in relation to the targets.
Government of India Ministry of Shipping and Transport
Government of India Ministry of Shipping and Transport